To solve for t, we need to isolate the variable t.
First, we add 1 to both sides of the equation:
2 + 1 = 3t − 1 + 1
3 = 3t
Next, divide both sides of the equation by 3 to solve for t:
3/3 = 3t/3
1 = t
Therefore, the solution is t = 1.
Solve for t.
2 = 3t − 1
t =
11 answers
Solve for u.
3u − 2 = 4
u =
3u − 2 = 4
u =
To solve for u, we need to isolate the variable u.
First, we add 2 to both sides of the equation:
3u − 2 + 2 = 4 + 2
3u = 6
Next, divide both sides of the equation by 3 to solve for u:
3u/3 = 6/3
u = 2
Therefore, the solution is u = 2.
First, we add 2 to both sides of the equation:
3u − 2 + 2 = 4 + 2
3u = 6
Next, divide both sides of the equation by 3 to solve for u:
3u/3 = 6/3
u = 2
Therefore, the solution is u = 2.
Solve for t.
3 + 2t = 5
t =
3 + 2t = 5
t =
To solve for t, we need to isolate the variable t.
First, subtract 3 from both sides of the equation:
3 + 2t - 3 = 5 - 3
2t = 2
Next, divide both sides of the equation by 2 to solve for t:
2t/2 = 2/2
t = 1
Therefore, the solution is t = 1.
First, subtract 3 from both sides of the equation:
3 + 2t - 3 = 5 - 3
2t = 2
Next, divide both sides of the equation by 2 to solve for t:
2t/2 = 2/2
t = 1
Therefore, the solution is t = 1.
Solve for y. –6 = y/2 + –5 y =
To solve for y, we need to isolate the variable y.
First, add 5 to both sides of the equation:
-6 + 5 = y/2 + -5 + 5
-1 = y/2
Next, multiply both sides of the equation by 2 to solve for y:
2 * -1 = 2 * (y/2)
-2 = y
Therefore, the solution is y = -2.
First, add 5 to both sides of the equation:
-6 + 5 = y/2 + -5 + 5
-1 = y/2
Next, multiply both sides of the equation by 2 to solve for y:
2 * -1 = 2 * (y/2)
-2 = y
Therefore, the solution is y = -2.
Solve for g. 4g − 12 = 8 g =
To solve for g, we need to isolate the variable g.
First, add 12 to both sides of the equation:
4g - 12 + 12 = 8 + 12
4g = 20
Next, divide both sides of the equation by 4 to solve for g:
4g/4 = 20/4
g = 5
Therefore, the solution is g = 5.
First, add 12 to both sides of the equation:
4g - 12 + 12 = 8 + 12
4g = 20
Next, divide both sides of the equation by 4 to solve for g:
4g/4 = 20/4
g = 5
Therefore, the solution is g = 5.
Solve for m. 18.23 = 3m + 3.92 m =
To solve for m, we need to isolate the variable m.
First, subtract 3.92 from both sides of the equation:
18.23 - 3.92 = 3m + 3.92 - 3.92
14.31 = 3m
Next, divide both sides of the equation by 3 to solve for m:
14.31/3 = 3m/3
m ≈ 4.77
Therefore, the solution is m ≈ 4.77.
First, subtract 3.92 from both sides of the equation:
18.23 - 3.92 = 3m + 3.92 - 3.92
14.31 = 3m
Next, divide both sides of the equation by 3 to solve for m:
14.31/3 = 3m/3
m ≈ 4.77
Therefore, the solution is m ≈ 4.77.